The complete chloroplast genome sequence of an important medicinal plant Cynanchum wilfordii (Maxim.) Hemsl. (Apocynaceae). (2nd September 2016) - Park, Hyun-Seung; Kim, Kyu-Yeob; Kim, Kyunghee; Lee, Sang-Choon; Lee, Junki; Seong, Rack Seon; Shim, Young Hun; Sung, Sang Hyun; Yang, Tae-Jin
Abstract: Cynanchum wilfordii (Maxim.) Hemsl. is a traditional medicinal herb belonging to the Asclepiadoideae subfamily, whose dried roots have been used as traditional medicine in Asia. The complete chloroplast genome of C. wilfordii was generated by de novo assembly using the small amount of whole genome sequencing data. The chloroplast genome of C. wilfordii was 161 241 bp long, composed of large single copy region (91 995 bp), small single copy region (19 930 bp) and a pair of inverted repeat regions (24 658 bp). The overall GC contents of the chloroplast genome was 37.8%. A total of 114 genes were annotated, which included 80 protein-coding genes, 30 tRNA genes and 4 rRNA genes. Phylogenetic analysis with the reported chloroplast genomes revealed that C. wilfordii is most closely related to Asclepias nivea (Caribbean milkweed) and Asclepias syriaca (common milkweed) within the Asclepiadoideae subfamily.